2015
DOI: 10.1038/bonekey.2015.66
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Type I collagen microstructure induced by estrogen depletion can be prevented with drug treatment

Abstract: Two independent biological replicates of estrogen depletion were employed with differing drug treatment conditions. Data Set I consisted of 9-month-old New Zealand white female rabbits treated as follows: sham-operated (n ¼ 11), ovariectomized (OVX; n ¼ 12), OVX þ 200 mg kg À 1 alendronate (ALN), 3 Â a week for 27 weeks (n ¼ 12) and OVX þ 10 mg kg À 1 Cathepsin-K inhibitor (CatKI) daily for 27 weeks. Data Set II consisted of 6-month-old New Zealand white female rabbits that were sham-operated (n ¼ 12), OVX (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…We have demonstrated non-Gaussian distributions in collagen nanomorphology with D -spacing measured from 59 to 75 nm. 1320 We found that, in general, there is very little variation in D -spacings within bundles (groups of aligned fibrils) but large variations between bundles. 18 Existing models of collagen structure cannot explain these D -spacing distributions, but a recent study documented changes in collagen structure at all levels of hierarchy, including D -spacing, as a function of disease.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…We have demonstrated non-Gaussian distributions in collagen nanomorphology with D -spacing measured from 59 to 75 nm. 1320 We found that, in general, there is very little variation in D -spacings within bundles (groups of aligned fibrils) but large variations between bundles. 18 Existing models of collagen structure cannot explain these D -spacing distributions, but a recent study documented changes in collagen structure at all levels of hierarchy, including D -spacing, as a function of disease.…”
Section: Introductionmentioning
confidence: 79%
“…20 We documented surface heterogeneity and changes in collagen microstructure that would not be reflected in average values incorporating measurements from many fibrils over a larger area of the tissue surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rabbit cortical femur images analyzed were from our previously published data set (Cauble et al, 2015). There were a total of 663 images (3.5 μm 2 ) for cortical femur samples taken from 48 animals (11 Sham, 12 OVX + Veh, 12 OVX + ALN, and 13 OVX + CatKI).…”
Section: Methodsmentioning
confidence: 99%